Does shelter enhance early seedling survival in dry environments? A test with eight Mediterranean species - Padilla, Francisco M; Miranda, Juan de Dios; Ortega, Rafael; Hervás, Manuel; Sánchez, Joaquín; Pugnaire, Francisco I (Applied Vegetation Science, 2011)
Question: Do solid-walled polyethylene tubes and mesh fabric tubes improve the short-term survival of eight Mediterranean tree and shrub species often used in the restoration of arid environments? Location: We conducted two experimental plantations in degraded field sites in the province of Almería (SE Spain), under arid Mediterranean conditions. Methods: One-year-old seedlings of Ceratonia siliqua, Juniperus phoenicea, Olea europaea, Pinus halepensis, Pinus pinaster, Quercus coccifera, Quercus ilex and Tetraclinis articulata were planted either sheltered by one of the above shelter tubes, or by being left unsheltered. Survival was recorded the first growing season after planting, which was a very dry season. Results: Overall, seedling survival ranged from as little as 0% to 24%, and tree shelters consistently enhanced survival in Quercus species only, ranging from 16% in walled shelters to 8% in mesh shelters. Shelters failed to boost survival in the six remaining species. Conclusion: The results of this study suggest that both walled and mesh shelters were mostly ineffective at increasing seedling survival for the Mediterranean species used in this experiment; these species coincide with those used in restoration programs. The use of shelters in restoration programs conducted in arid environments should be reconsidered, while walled shelters might be advisable for Mediterranean Quercus species only. Further research is necessary to develop and assess improved types of shelters for arid environments.
Keywords: Arid environments; Drought; Forest restoration; tree shelters; woody seedlings

Ecophysiological Traits Associated with Drought in Mediterranean Tree Seedlings: Individual Responses versus Interspecific Trends in Eleven Species - Valladares, F.; Sánchez-Gómez, D. (Plant Biology, 2006)
Abstract: Species differ regarding their drought tolerance and individuals of a given species can modify their morphology and physiology in response to drought. However, since evolutionary and ecological selective pressures differ, individual and interspecific responses to drought might not match. We determined summer survival and a number of ecophysiological variables in two factorial experiments with seedlings of eleven tree species present in Mediterranean ecosystems, grown under slowly imposed water stress and control conditions. Plants experiencing drought exhibited reduced growth, low specific leaf area, chlorophyll content, and photosynthetic rate when compared to the controls, and species-specific drought tolerance was associated with an analogous set of trait values. However, while species with high leaf area ratio and shoot-root ratio exhibited greater drought tolerance, drought induced the reversed response within species. Contrary to expectations, water use efficiency was lower in drought-tolerant species and decreased in water-stressed individuals compared to the control plants. There was a distinctive phylogenetic signal in the functional grouping of species, with oaks, pines, and other genera being clearly different from each other in their drought tolerance and in their functional responses to drought. However, all relationships between ecophysiological variables and drought tolerance were significant after accounting for phylogenetic effects, with the exception of the relationship between drought tolerance and photochemical efficiency. Our results show that drought tolerance is not achieved by a single combination of trait values, and that even though evolutionary processes and individual responses tend to render similar results in terms of functional traits associated with drought, they do not necessarily match.
The following values have no corresponding Zotero field: publisher: Blackwell Publishing Ltd
Keywords: Drought tolerance; functional traits; Mediterranean plants; phylogeny; water use efficiency; woody seedlings

Ecophysiological Traits Associated with Drought in Mediterranean Tree Seedlings: Individual Responses versus Interspecific Trends in Eleven Species - Valladares, F; Sánchez-Gómez, D (Plant Biology, 2006)
Abstract: Species differ regarding their drought tolerance and individuals of a given species can modify their morphology and physiology in response to drought. However, since evolutionary and ecological selective pressures differ, individual and interspecific responses to drought might not match. We determined summer survival and a number of ecophysiological variables in two factorial experiments with seedlings of eleven tree species present in Mediterranean ecosystems, grown under slowly imposed water stress and control conditions. Plants experiencing drought exhibited reduced growth, low specific leaf area, chlorophyll content, and photosynthetic rate when compared to the controls, and species-specific drought tolerance was associated with an analogous set of trait values. However, while species with high leaf area ratio and shoot-root ratio exhibited greater drought tolerance, drought induced the reversed response within species. Contrary to expectations, water use efficiency was lower in drought-tolerant species and decreased in water-stressed individuals compared to the control plants. There was a distinctive phylogenetic signal in the functional grouping of species, with oaks, pines, and other genera being clearly different from each other in their drought tolerance and in their functional responses to drought. However, all relationships between ecophysiological variables and drought tolerance were significant after accounting for phylogenetic effects, with the exception of the relationship between drought tolerance and photochemical efficiency. Our results show that drought tolerance is not achieved by a single combination of trait values, and that even though evolutionary processes and individual responses tend to render similar results in terms of functional traits associated with drought, they do not necessarily match.
Keywords: Drought tolerance; functional traits; Mediterranean plants; phylogeny; water use efficiency; woody seedlings